Effets de l’érosion du sable sur les performances d'une éolienne. - REZIG Ahmida (Bibliotheque centrale -Unversite de Laghouat, 2020)
Abstract. This paper presents the results of experimental research to investigate blade material surface deterioration of wind turbines located in arid areas caused by sand particles impacts and the resulting influence on their energetic performance. Tests are conducted in the erosion sandblaster then in the wind tunnel for uncoated Glass Fiber/Polyester blade at various angles and durations impact. The magnitudes of aerodynamics forces on a Naca 4412 profile are determined experimentally. All profiles (AR=0.571) are tested in a wind tunnel at air speed of 10 m/s at Reynolds number 6.5 x 105. The results show the behavioral differences detected for the specimens with T =160 s, T = 240 s and T = 340 s (when Ra increases) by comparing them with the smooth specimen (T = 0 s, Ra= 0.94). Force coefficients (CL and CD) show significant changes which leads to a decrease of the lift-todrag ratio and therefore there will be a notable performance loss. This will be an acceptable threshold for the case where t = 160s